2021
DOI: 10.7759/cureus.12973
|View full text |Cite
|
Sign up to set email alerts
|

Does Social Stigma and Neglect Post-COVID-19 Matter? A Case Report on Brief Psychotic Disorder Post-COVID-19 and Self-Quarantine

Abstract: Social stigma and neglect post-coronavirus disease 2019 (COVID-19) and self-quarantine can be associated with a brief psychotic disorder (BPD). A 53-year-old African-American man with no significant past medical and psychiatric history was brought to the emergency department (ED) with symptoms of persecutory delusions post COVID-19 and self-quarantine. His symptoms included false beliefs that people were plotting to kill him which made him combative at work and home. As his symptoms worsened, his wife brought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Finally, 18 articles did not include individual level data and 7 articles were available as abstracts only. A total of 40 articles met inclusion criteria, comprising 48 individual patients from 17 countries ( Table 1 ) [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ]. All but a single study [ 54 ] were in English and 20 (42%) cases were reported in the United States, where the largest proportion of these cases were documented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 18 articles did not include individual level data and 7 articles were available as abstracts only. A total of 40 articles met inclusion criteria, comprising 48 individual patients from 17 countries ( Table 1 ) [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ]. All but a single study [ 54 ] were in English and 20 (42%) cases were reported in the United States, where the largest proportion of these cases were documented.…”
Section: Resultsmentioning
confidence: 99%
“… Reported Dx: psychosis and depression; catatonia DSM-5 Dx: Psychotic disorder due to COVID-19, with delusions; catatonia due to COVID-19 Recent treatment with steroids preceding psychosis. Baral et al, 2021 [ 30 ] 53, M, US After 5 weeks of COVID-19, he experienced delusional thoughts that people, including his wife, were plotting to kill him. Fever, cough and weakness for 2 days None None + SARS-Cov-2 PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Eight ( Hansen et al 2020 , Alba et al 2021 , Noone et al 2020 (a), Kozato et al 2021 , Smith et al 2020 , Lim et al 2020 , Majadas et al 2020 , Baral et al 2021 ) have reported COVID-19 like illness prior to onset of psychotic symptoms. Eight have not shared the details regarding duration passed between a positive RT PCR swab and onset of psychosis (Sanchez et al 2020, Parker et al 2021 , Kozato et al 2021 , Lannier et al 2020, Majadas et al 2020 , Correa- et al 2020, Ferrando et al 2020 , Saje et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, other studies have shown that people feel a deep sense of exclusion due to stigma (69), which causes mental disorders (70). Furthermore, social stigma affects women's health by being a prominent barrier to diagnostic and treatment procedures for improving mental health problems such as anxiety and depression (71).…”
Section: Discussionmentioning
confidence: 99%